FORMING INDICATORS FOR CSR PROGRAM, INNOVATION, LEARNING ORIENTATION AND PERFORMANCE SMES’’ IN MALANG (International Conference of Graduate School on Sustainability (ICGSS), 2018)
The purpose of this study is to study the confirmatory factors of CSR programs, SME innovation, learning orientation and the performance of Small and Medium Enterprises in Malang City. The unit of analysis used is Small and Medium Enterprises (SMEs’) in Malang City that get 198 government and private CSR programs from 198 SMEs’’. Analytical tools used are confirmatory factor analysis (CFA) techniques. The results show that the strongest environmental oriented CSR indicators as a form of variable corporate social responsibility (CSR). Indicator of process innovation is the most dominant indicator in measuring SME innovation variables. The commitment to learning indicator is the most dominant indicator in measuring learning orientation variables. Financial performance indicators are the most dominant indicator in measuring SME performance variables.